Efficacy and community effectiveness of larvivorous fish for dengue vector control. Issue 9 (3rd June 2015) - Han, W. W.; Lazaro, A.; McCall, P. J.; George, L.; Runge‐Ranzinger, S.; Toledo, J.; Velayudhan, R.; Horstick, O.
Abstract Objective To evaluate the efficacy and community effectiveness of larvivorous fish for the control of dengue vectors and dengue transmission, when used as a single agent or in combination with other vector control methods. Method Comprehensive literature search of published and grey literature using PubMed, EMBASE (DMDI), Web of Science, WHOLIS, WILEY, LILACS, GIFT, Cochrane Library, ELDIS, New York Academy of Medicine Grey Literature Report and Google. All results were checked for duplicates and examined for eligibility. Methodological quality of the studies was assessed using RoBANS. Results Thirteen articles were considered eligible for inclusion. Incorporating a wide range of interventions and outcome measures, three were efficacy studies and 10 assessed community effectiveness. None of the studies were randomised or cluster‐randomised controlled trials. All three efficacy studies and seven community effectiveness studies investigated fish as a single agent. All efficacy studies reported elimination of Aedes larvae from treated containers, while community effectiveness studies reported reductions in immature vector stages, two of which also detected a continuous decline over 2 years. An impact on adult mosquitoes was shown in only two community effectiveness studies. Reductions in dengue cases following intervention were reported in two studies, but it was not possible to attribute this to the intervention. Conclusion While the use of larvivorous fish as a single agent or in combination with other control measures could lead to reductions in immature vector stages, considerable limitations in all the studies restricted any conclusions with respect to the evaluation of community effectiveness. Evidence for the community effectiveness of larvivorous fish as a single agent remains minimal and cluster‐randomised controlled studies that include the assessment of impact on dengue are recommended.